Structure and Fc-Effector Function of Rhesusized Variants of Human Anti-HIV-1 IgG1s - Tolbert, William D.; Nguyen, Dung N.; Tuyishime, Marina; Crowley, Andrew R.; Chen, Yaozong; Jha, Shalini; Goodman, Derrick; Bekker, Valerie; Mudrak, Sarah V.; DeVico, Anthony L.; Lewis, George K.; Theis, James F.; et al. (Frontiers in Immunology, 2022)
Passive transfer of monoclonal antibodies (mAbs) of human origin into Non-Human Primates (NHPs), especially those which function predominantly by a Fc-effector mechanism, requires an a priori preparation step, in which the human mAb is reengineered to an equivalent NHP IgG subclass. This can be achieved by changing both the Fc and Fab sequence while simultaneously maintaining the epitope specificity of the parent antibody. This Ab reengineering process, referred to as rhesusization, can be challenging because the simple grafting of the complementarity determining regions (CDRs) into an NHP IgG subclass may impact the functionality of the mAb. Here we describe the successful rhesusization of a set of human mAbs targeting HIV-1 envelope (Env) epitopes involved in potent Fc-effector function against the virus. This set includes a mAb targeting a linear gp120 V1V2 epitope isolated from a RV144 vaccinee, a gp120 conformational epitope within the Cluster A region isolated from a RV305 vaccinated individual, and a linear gp41 epitope within the immunodominant Cys-loop region commonly targeted by most HIV-1 infected individuals. Structural analyses confirm that the rhesusized variants bind their respective Env antigens with almost identical specificity preserving epitope footprints and most antigen-Fab atomic contacts with constant regions folded as in control RM IgG1s. In addition, functional analyses confirm preservation of the Fc effector function of the rhesusized mAbs including the ability to mediate Antibody Dependent Cell-mediated Cytotoxicity (ADCC) and antibody dependent cellular phagocytosis by monocytes (ADCP) and neutrophils (ADNP) with potencies comparable to native macaque antibodies of similar specificity. While the antibodies chosen here are relevant for the examination of the correlates of protection in HIV-1 vaccine trials, the methods used are generally applicable to antibodies for other purposes.